Culture and Adat in Globalizational Era - I Made Suwitra (Fakultas Hukum, Universitas Warmadewa, 2018)
Tradition is one element of the form of culture as the identity of a society. Understanding adat as a form of community culture can accelerate the process of unity and unity of the nation as Indonesia which is composed of various cultures and its tradition.This diversity becomes the strength of the Indonesian nation that must always be knitted, so it must be managed with the spirit of nationality based on Pancasila and 1945 Constitution in the container Bhineka Tunggal Ikadan The Unitary State, because if it is not managed properly and properly it can lead to the disintegration of the nation and threaten the integrity of the Unitary State of the Republic of Indonesia. Differences of custom and culture also apply globally and tested in the era of globalization. Therefore it is necessary to understand the reality of the differences to be managed in creating peace.